Preparation method of BC-BiOBr-OV nano composite material

The BC-BiOBr-OV nanocomposite was constructed by combining biochar with oxygen-rich vacancies by solvothermal method, which solved the problem of insufficient performance of BiOBr composite catalysts in the prior art in photocatalytic activation of PDS to degrade organic pollutants, and achieved the effect of significantly improving catalytic activity and carrier separation efficiency.

CN119702017AActive Publication Date: 2025-03-28HUBEI RIXI TECHNOLOGY DEVELOPMENT CO LTD

Patent Information

Application Number
CN202411824804.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

In the prior art, the oxygen-rich BiOBr composite catalyst has a relatively lack of performance in photocatalyzing PDS to degrade organic pollutants.

Method used

The BC-BiOBr-OV nanocomposite was constructed by combining wood chip carbonized biochar (BC) with oxygen-rich BiOBr by solvothermal method to improve its catalytic activity and carrier separation efficiency.

Benefits of technology

It significantly improves the adsorption and activation ability of BiOBr matrix materials to molecular oxygen, improves its energy band structure and separation and migration ability of photogenerated electrons and holes, improves catalytic activity, and is suitable for photocatalytic activation of PDS to degrade organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702017A_ABST
    Figure CN119702017A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a BC-BiOBr-OV nano composite material, which comprises the following steps: preparing BC by using sawdust as a raw material and an H2SO4 solution as a solvent and adopting a calcination method; according to the method, Bi (NO3) 3.5 H2O, BC and KBr are taken as raw materials, ethylene glycol is taken as a solvent, and then charcoal obtained by carbonizing wood chips is combined with BiOBr rich in oxygen vacancies by adopting a solvothermal method, so that the BC-BiOBr-OV nano composite material which is stable in structure, large in specific surface area, high in visible light response capability, high in carrier separation efficiency and rich in catalytic active sites is constructed. The obtained BC-BiOBr-OV nano composite material has the advantages of stable structure, large specific surface area, strong visible light response capability, high carrier separation efficiency, rich catalytic active sites and the like, and is expected to be applied to photocatalytic activation of persulfate (hereinafter PS is used) to degrade organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental pollution control, and in particular to a BC-BiOBr-O V Method for preparing nanocomposite materials. Background Art

[0002] BiOBr has a staggered structure of [B2O2] sheets and double Bi sheets, containing staggered anions and anionic groups, which can induce the generation of internal electrostatic fields and promote the separation of photogenerated carriers. It is well known that oxygen vacancies with abundant localized electrons can significantly promote the adsorption and activation of molecular oxygen, so the catalytic activity of BiOBr can be optimized by constructing surface oxygen vacancies. At present, a variety of methods have been successfully used to prepare BiOBr nanomaterials and a large number of research reports on the degradation of various pollutants by BiOBr materials have been published. However, there are few reports on the performance of BiOBr composite catalysts rich in oxygen vacancies in photocatalytic activation of PDS to degrade organic pollutants.

[0003] BC has an ideal pore structure and specific surface area, rich surface functional groups and mineral elements, which give it good catalytic potential. Combining BC with different nano-metal oxides / hydroxides can, on the one hand, give full play to the advantages of BC's large specific surface area, so that it can better disperse metal / metal oxide nanoparticles, make the composite magnetic, and facilitate recovery; on the other hand, BC can provide catalytic active sites, such as oxygen-containing functional groups, nitrogen groups, and defect edges, to enhance catalytic activity. In addition, BC can also effectively inhibit the overflow of metal ions and improve the stability of the catalyst. Therefore, combining BC with BiOBr rich in oxygen vacancies to further improve the carrier separation efficiency and catalytic activity is an effective strategy to improve catalytic efficiency. The preparation of BC-BiOBr-O by solvothermal method V Little is known about the performance of nanocomposites for photocatalytic activation of PDS for degradation of organic pollutants. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problems existing in the prior art and provide a BC-BiOBr-O V Method for preparing nanocomposite materials.

[0005] To achieve the above object, the technical solution provided by the present invention is: a BC-BiOBr-O V The invention discloses a method for preparing a nanocomposite material, wherein the method combines biochar carbonized from sawdust with BiOBr rich in oxygen vacancies by a solvothermal method, thereby constructing a BC-BiOBr-O nanocomposite material with stable structure, large specific surface area, strong visible light response ability, high carrier separation efficiency and rich catalytic active sites. VThe nanocomposite material, the preparation method has the following specific steps:

[0006] Step (1): after sieving sawdust at a certain mesh size, soak the sawdust in an appropriate amount of 60-90wt.% H2SO4 solution at a certain solid-liquid ratio, and continue stirring at room temperature for 10-240 minutes to obtain a solid-liquid mixture;

[0007] Step (2): adding an appropriate amount of deionized water to the solid-liquid mixture obtained in step (1) to dilute the solution to 5-50wt.%, then transferring it to an oven, keeping it at a certain temperature for 20-240 minutes, cooling it naturally, filtering and washing it until it is neutral, and then drying it at a certain temperature for 6-24 hours to obtain sawdust;

[0008] Step (3): grinding the sawdust obtained in step (2), sieving it under a certain mesh condition, and finally transferring it to a tube furnace, heating it to a holding temperature under a N2 atmosphere, and keeping it at the holding temperature for 30-360 minutes to obtain BC;

[0009] Step (4): dissolving a certain amount of Bi(NO3)3·5H2O in a certain amount of ethylene glycol solution, stirring continuously for 10-120 min to obtain a mixed solution;

[0010] Step (5): dissolve a certain amount of KBr and the BC in step (3) in a certain amount of ethylene glycol solution, and perform ultrasonic treatment for 10-120 min;

[0011] Step (6): Add the solution obtained in step (5) dropwise into the mixed solution obtained in step (4), continue stirring for 30-360 min, and then quickly fill with N2 for a certain period of time;

[0012] Step (7): The solution obtained in step (6) is transferred to a hydrothermal reactor, heated to a certain insulation temperature, and kept at the insulation temperature for 12-48 hours. After naturally cooling to room temperature, the sample is centrifuged and washed, and finally vacuum dried at a certain temperature for 6-24 hours to obtain BC-BiOBr-O V Nanocomposite materials.

[0013] Preferably, in step (1), the sawdust screening requirement is 30-90 mesh, and the solid-liquid ratio of sawdust to H2SO4 solution is 1-30%.

[0014] Preferably, the insulation temperature in step (2) is 80-300°C, and the drying temperature is 50-250°C.

[0015] Preferably, in step (3), the sawdust screening requirement is 60-150 mesh, and the insulation temperature is 400-800°C.

[0016] Preferably, the mass of Bi(NO3)3·5H2O used in step (4) is 1-20 g, and the volume of ethylene glycol is 30-600 mL.

[0017] Preferably, the mass of BC used in step (5) is 0-10 g, the mass of KBr is 0.1-10 g, and the volume of ethylene glycol is 10-400 mL.

[0018] Preferably, the time for charging N2 in step (6) is 1-30 min.

[0019] Preferably, the insulation temperature in step (7) is 120-400°C, and the vacuum drying temperature is 40-90°C.

[0020] Beneficial effects of the present invention:

[0021] The present invention combines biochar carbonized from sawdust with BiOBr rich in oxygen vacancies by a solvothermal method to construct BC-BiOBr-O V The nanocomposite material significantly improves the adsorption and activation ability of BiOBr matrix material for molecular oxygen, and successfully improves its band structure and the separation and migration ability of photogenerated electrons and holes. The preparation process is simple and the production cost is low. V Nanocomposites have the advantages of stable structure, large specific surface area, strong visible light response ability, high carrier separation efficiency and abundant catalytic active sites, and are expected to be used in photocatalytic activation of persulfate to degrade organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0023] Figure 1 The XRD patterns of the samples prepared in Examples 1 to 4 of the present invention are as follows;

[0024] Figure 2 It is 4BC-BiOBr-O obtained in Examples 1 to 4 of the present invention. V TEM images of the nanocomposites at different magnifications;

[0025] Figure 3 It is a rate diagram of the sample obtained in the embodiment of the present invention activating PDS to degrade tetracycline (hereinafter referred to as TC);

[0026] Figure 4 It is a graph showing the rate of degradation of rhodamine B (hereinafter referred to as RhB) by activating PDS with the samples obtained in the examples of the present invention. DETAILED DESCRIPTION

[0027] This section will describe in detail the specific embodiments of the present invention. The preferred embodiments of the present invention are shown in the accompanying drawings. The purpose of the accompanying drawings is to supplement the description of the text part of the specification with graphics, so that people can intuitively and vividly understand each technical feature and the overall technical solution of the present invention, but it cannot be understood as a limitation on the scope of protection of the present invention.

[0028] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.

[0029] Reference Figure 1-Figure 4 , a preferred embodiment of the present invention, a BC-BiOBr-O V A method for preparing a nanocomposite material, wherein the method adopts a solvothermal method to prepare BiOBr-biochar (hereinafter referred to as BC-BiOBr- V ) nanocomposite materials, using sawdust as raw material and H2SO4 solution as solvent, BC was prepared by calcination method; using Bi(NO3)3·5H2O, BC and KBr as raw materials and ethylene glycol as solvent, biochar carbonized from sawdust was combined with BiOBr rich in oxygen vacancies by solvothermal method, thus constructing BC-BiOBr-O with stable structure, large specific surface area, strong visible light response ability, high carrier separation efficiency and rich catalytic active sites. V Nanocomposite materials.

[0030] The obtained BC-BiOBr-O V Nanocomposites have the advantages of stable structure, large specific surface area, strong visible light response ability, high carrier separation efficiency and abundant catalytic active sites, and are expected to be applied to photocatalytic activation of persulfate (hereinafter referred to as PS) to degrade organic pollutants.

[0031] Example 1

[0032] A BC-BiOBr-O V Method for preparing nanocomposite materials.

[0033] (1) Take 6g of sawdust sieved through 50 mesh, soak it in 80wt% H2SO4 solution with a solid-liquid ratio of 15% by volume, stir it at room temperature for 2h, add appropriate amount of deionized water to dilute the H2SO4 solution to 20wt%, then put it into an oven, keep it at 140℃ for 2h, wait for natural cooling, filter and wash the obtained product until it is neutral, and dry it at 120℃ for 8h. After grinding the dried sawdust and sieving it through 120 mesh, transfer it to a tube furnace under N2 atmosphere, keep it at 550℃ for 2h, and finally obtain BC;

[0034] (2) Take 7.76g Bi(NO3)3·5H2O and dissolve it in 200mL ethylene glycol, and stir it continuously for 60min to obtain solution A1; take 0g BC and 1.90g KBr and dissolve them in 80mL ethylene glycol, and ultrasonicate for 60min to obtain solution B1. Add solution B1 dropwise into solution A1, stir it continuously for 2h, and then quickly fill it with N2 for 10min. Then transfer the obtained solution to a hydrothermal reactor and keep it at 220℃ for 22h. After cooling naturally, wash the obtained product with deionized water and ethanol, and centrifuge it. Finally, dry it in a vacuum environment at 80℃ for 6h to obtain 0BC-BiOBr-O with a total mass fraction of BC of 0%. V Nanocomposite materials (hereinafter referred to as BiOBr-O V ).

[0035] Example 2

[0036] A BC-BiOBr-O V Method for preparing nanocomposite materials.

[0037] (1) Take 8g of sawdust sieved through 60 mesh, soak it in a 75wt% H2SO4 solution with a solid-liquid ratio of 10% by volume, stir it at room temperature for 1h, add an appropriate amount of deionized water to dilute the H2SO4 solution to 15wt%, then put it into an oven, keep it at 120℃ for 1h, wait for natural cooling, filter and wash the obtained product until it is neutral, and then dry it at 105℃ for 10h. After grinding the dried sawdust and sieving it through 100 mesh, transfer it to a tube furnace under N2 atmosphere, keep it at 600℃ for 1h, and finally obtain BC;

[0038] (2) 3.88 g Bi(NO3)3·5H2O was dissolved in 100 mL ethylene glycol and stirred for 30 min to obtain solution A2; 0.19 g BC and 0.95 g KBr were dissolved in 40 mL ethylene glycol and ultrasonicated for 30 min to obtain solution B2. Solution B2 was added dropwise to solution A2 and stirred for 1 h. N2 was quickly filled in for 5 min and the obtained solution was transferred to a hydrothermal reactor and kept at 200 °C for 24 h. After natural cooling, the obtained product was washed with deionized water and ethanol and centrifuged. Finally, it was dried in a vacuum environment at 60 °C for 8 h to obtain 4BC-BiOBr-O with a total mass fraction of BC of 4%. V Nanocomposite materials.

[0039] Example 3

[0040] A BC-BiOBr-O V Method for preparing nanocomposite materials.

[0041] (1) Take 10g of sawdust sieved through 70 mesh, soak it in 70wt% H2SO4 solution with a solid-liquid ratio of 8% by volume, stir it at room temperature for 3h, add appropriate amount of deionized water to dilute the H2SO4 solution to 10wt%, then put it into an oven, keep it at 160℃ for 1.5h, wait for natural cooling, filter and wash the obtained product until it is neutral, and dry it at 140℃ for 7h. After grinding the dried sawdust and sieving it through 140 mesh, transfer it to a tube furnace under N2 atmosphere, keep it at 550℃ for 1.5h, and finally obtain BC;

[0042] (2) Take 5.82g Bi(NO3)3·5H2O and dissolve it in 150mL ethylene glycol, and stir it continuously for 45min to obtain solution A3; take 0.79g BC and 1.43g KBr and dissolve them in 60mL ethylene glycol, and ultrasonicate them for 45min to obtain solution B3. Solution B3 was added dropwise to solution A3, and after stirring continuously for 1.5h, N2 was quickly filled in and maintained for 15min. The obtained solution was then transferred to a hydrothermal reactor and kept warm at 250℃ for 20h. After natural cooling, the obtained product was washed with deionized water and ethanol, and centrifuged, and finally dried in a vacuum environment at 70℃ for 7h to obtain 12BC-BiOBr-O with a total mass fraction of BC of 12%. V Nanocomposite materials.

[0043] Example 4

[0044] To test the photocatalytic activity, first prepare the concentration of 20 mg·L -1 TC solution and the concentration is 20 mg·L -1 RhB solution, add appropriate amount of BC-BiOBr-O V The nanocomposite material was added with 200 mL of 20 mg·L -1 In a 250mL flat-bottomed beaker containing TC or RhB reaction solution, the pH of the solution was adjusted by 0.1M HCl / NaOH solution, and a 300WXe lamp with a 420nm filter was used as the light source. The photocatalytic activation of PDS to degrade TC or RhB was carried out under mechanical stirring at 300rpm and circulating water conditions. After a certain time interval (5min), 2mL of the reaction sample was collected with a syringe, the catalyst was filtered through a 0.22μm water filter membrane, and then an equal volume of methanol was quickly added to terminate the degradation reaction. Finally, the collected reaction samples were measured by UV-visible absorption method to determine the concentration of TC or RhB solution during the photocatalytic process at different times to calculate the rate of photocatalytic activation of PDS to degrade TC or RhB. For the recovery experiment, the catalyst sample was recovered by centrifugation, washed several times with distilled water, and then dried and collected to store the sample.

[0045] Under the premise that no conflict occurs, those skilled in the art may freely combine and superimpose the above-mentioned additional technical features.

[0046] The above description is only a preferred implementation mode of the present invention. Any technical solution that achieves the purpose of the present invention by substantially the same means belongs to the protection scope of the present invention.

Claims

1. A BC-BiOBr-O V The method for preparing a nanocomposite material is characterized by: The preparation method uses a solvothermal method to combine biochar carbonized from sawdust with BiOBr rich in oxygen vacancies, thereby constructing BC-BiOBr-O with stable structure, large specific surface area, strong visible light response ability, high carrier separation efficiency and rich catalytic active sites. V The nanocomposite material, the preparation method has the following specific steps: Step (1): after sieving sawdust at a certain mesh size, soak the sawdust in an appropriate amount of 60-90wt.% H2SO4 solution at a certain solid-liquid ratio, and continue stirring at room temperature for 10-240 minutes to obtain a solid-liquid mixture; Step (2): adding an appropriate amount of deionized water to the solid-liquid mixture obtained in step (1) to dilute the solution to 5-50wt.%, then transferring it to an oven, keeping it at a certain temperature for 20-240 minutes, cooling it naturally, filtering and washing it until it is neutral, and then drying it at a certain temperature for 6-24 hours to obtain sawdust; Step (3): grinding the sawdust obtained in step (2), sieving it under a certain mesh condition, and finally transferring it to a tube furnace, heating it to a holding temperature under a N2 atmosphere, and keeping it at the holding temperature for 30-360 minutes to obtain BC; Step (4): dissolving a certain amount of Bi(NO3)3·5H2O in a certain amount of ethylene glycol solution, stirring continuously for 10-120 min to obtain a mixed solution; Step (5): dissolve a certain amount of KBr and the BC in step (3) in a certain amount of ethylene glycol solution, and perform ultrasonic treatment for 10-120 min; Step (6): Add the solution obtained in step (5) dropwise into the mixed solution obtained in step (4), continue stirring for 30-360 min, and then quickly fill with N2 for a certain period of time; Step (7): The solution obtained in step (6) is transferred to a hydrothermal reactor, heated to a certain insulation temperature, and kept at the insulation temperature for 12-48 hours. After naturally cooling to room temperature, the sample is centrifuged and washed, and finally vacuum dried at a certain temperature for 6-24 hours to obtain BC-BiOBr-O V Nanocomposite materials.

2. A BC-BiOBr-O according to claim 1 V The method for preparing a nanocomposite material is characterized by: In step (1), the sawdust screening requirement is 30-90 mesh, and the solid-liquid ratio of the sawdust to the H2SO4 solution is 1-30%.

3. A BC-BiOBr-O according to claim 1 V The method for preparing a nanocomposite material is characterized by: The insulation temperature in step (2) is 80-300°C, and the drying temperature is 50-250°C.

4. A BC-BiOBr-O according to claim 1 V The method for preparing a nanocomposite material is characterized by: In step (3), the sawdust screening requirement is 60-150 mesh and the insulation temperature is 400-800°C.

5. A BC-BiOBr-O according to claim 1 V The method for preparing a nanocomposite material is characterized by: The mass of Bi(NO3)3·5H2O used in step (4) is 1-20 g, and the volume of ethylene glycol is 30-600 mL.

6. A BC-BiOBr-O according to claim 1 V The method for preparing a nanocomposite material is characterized by: The mass of BC used in step (5) is 0-10 g, the mass of KBr is 0.1-10 g, and the volume of ethylene glycol is 10-400 mL.

7. A BC-BiOBr-O according to claim 1 V The method for preparing a nanocomposite material is characterized by: The time for filling with N2 in step (6) is 1-30 minutes.

8. A BC-BiOBr-O according to claim 1 V The method for preparing a nanocomposite material is characterized by: The insulation temperature in step (7) is 120-400°C, and the vacuum drying temperature is 40-90°C.

Citation Information

Patent Citations

  • Preparation method of BiOBr / black phosphorus alkene hetero-junction nano composite material

    CN109569670A

  • Oxygen-vacancy-enriched Bi / Bi12O17Cl2 nanoflower photocatalyst as well as preparation method and application thereof

    CN118059895A

  • Method of producing organoselenium-based nanocomposite

    US12115524B1

  • Halogenated graphene nanoplatelets, and production and uses thereof

    WO2017004363A1

Cited By

  • Oxygen-resistant photocatalytic reduction carbon dioxide catalyst as well as preparation method and application thereof

    CN122343087A